Achievement Goal Orientation, Conformity dan Problematic Internet Use terhadap Academic Procrastination pada Pelajar SMK Di Provinsi Banten: Studi dengan Penerapan Multiple Regression - Mutiah, Diana; Wahyuni, Sufira; Bintang, Rahmat S. (Personifikasi: Jurnal Ilmu Psikologi, 2024)
Academic procrastination is an individuals tendency to delay or avoid completion of tasks in an academic context carried out consciously, resulting in failure to complete them on time. The magnitude of the impact of academic procrastination on the world of education in the learning process will determine the low quality of education and also the quality of the pupils. The study aims to test the impact of achievement goal orientation, conformity, and problematic internet use on academic procrastination in SMK students in Banten Province. The sample in the study consisted of 578 students, consisting of 318 male students and 260 female students, with an age range of 15–18 years (mean age = 15.93, SD = 0.92). The sampling method used in this study is nonprobability sampling. Data collection was done using the Tuckman Procrastination Scale, the Generalized Problematic Internet Use Scale 2 (GPIUS-2), the Conformity Scale, and the Achievement Goal Orientation Questionnaire. Construction validity testing for the entire research instrument is carried out using the confirmatory factor analysis method. (CFA). The data analysis in this study uses a multiple regression approach. The results show that there is a significant influence of achievement goal orientation, conformity, and problematic internet use together on academic procrastination. These results provide implications regarding academic procrastination among students and efforts or policies to prevent academic procrastination.